2010
DOI: 10.1021/la904788t
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Photochemistry in β-Cyclodextrin Hosts: A TREPR, NMR, and CIDNP Investigation

Abstract: A systematic investigation of the photochemistry and ensuing radical chemistry of three guest ketones encapsulated in randomly methylated beta-cyclodextrin (beta-CD) hosts is reported. Dibenzyl ketone (DBK), deoxybenzoin (DOB), and benzophenone (BP) triplet states are rapidly formed after photolysis at 308 nm. Time-resolved electron paramagnetic resonance (TREPR) spectroscopy, steady-state NMR spectroscopy, and time-resolved chemically induced nuclear polarization (TR-CIDNP) experiments were performed on the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…4−9 The HAT reaction in supramolecular host−guest complexes has been preponderantly investigated using ensemble spectroscopic techniques such as transient absorption spectroscopy, 4,5 timeresolved electron paramagnetic resonance, 6−9 and nuclear magnetic resonance. 9 Due to the exponential dependence of HAT on the reaction distance (r) with a large exponential decay factor of β (i.e., β = 25−40 Å −1 ), 10,11 HAT is extremely sensitive to r and occurs over an extremely narrow distance range. In CD complexes, guest molecules are loosely bound inside the CD cavity via noncovalent host−guest interactions.…”
Section: Introductionmentioning
confidence: 99%
“…4−9 The HAT reaction in supramolecular host−guest complexes has been preponderantly investigated using ensemble spectroscopic techniques such as transient absorption spectroscopy, 4,5 timeresolved electron paramagnetic resonance, 6−9 and nuclear magnetic resonance. 9 Due to the exponential dependence of HAT on the reaction distance (r) with a large exponential decay factor of β (i.e., β = 25−40 Å −1 ), 10,11 HAT is extremely sensitive to r and occurs over an extremely narrow distance range. In CD complexes, guest molecules are loosely bound inside the CD cavity via noncovalent host−guest interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved (TR) EPR is the method of choice for studying spin-polarized intermediates in solutions. [35][36][37][38][39][40] So far, only one paper was 3 published reporting TR EPR study in ILs. 41 Using photoexcited triplet molecule of Zntetraphenylporphyrin (ZnTPP) authors clearly demonstrated that high viscosity of ILs suppresses electron spin relaxation caused by diffusional rotation of ZnTPP.…”
Section: Introductionmentioning
confidence: 99%
“…Note, however, that A/E or E/A SCRP patterns refer to the rather long inter-radical distances and, as a result, rather small mean exchange values (e.g., comparable to hyperfine interactions). Contrary, if separation of radicals is restricted and they reside close to each other, e.g., diffuse or tumble at radical–radical distances <1 nm, the radical pair S–T – mechanism leads to an observation of net emissive TR EPR spectra, both in liquids and frozen solutions. Net emission due to SCRP is manifested especially clearly when one of the radical partners is rapidly rotating, as was theoretically considered in ref for the porphyrin–quinone SCRP coupled by strong-exchange interaction. Note that exactly this situation is expected for the SCRP of main-chain and oxo-acyl radicals formed in the bulk of the polymer.…”
Section: Resultsmentioning
confidence: 97%